Emerging investigators series: highly effective adsorption of organic aromatic molecules from aqueous environments by electronically sorted single-walled carbon nanotubes. Issue 2 (16th January 2017) - Rocha, John-David R.; Rogers, Reginald E.; Dichiara, Anthony B.; Capasse, Ryan C.
Abstract : The use of electronically sorted ( i.e. semiconducting or metallic) single-walled carbon nanotubes (SWCNTs) for the removal of organic compounds from aqueous environments is investigated. Abstract : The use of electronically sorted ( i.e. semiconducting or metallic) single-walled carbon nanotubes (SWCNTs) for the removal of organic compounds from aqueous environments is investigated. Chromatography techniques are used to separate the semiconducting type from the metallic type. Spectroscopy (including UV-visible) is employed to measure the uptake of 1-pyrenebutyric acid, diquat dibromide, and 2, 4-dichlorophenoxyacetic acid onto the sorted SWCNTs. Kinetic and equilibrium analysis show that the semiconducting type is capable of adsorbing up to 70.6% more adsorbate compared to the metallic type. This is likely attributed to the favorability of these compounds interacting with the semiconducting type due to a lack of electron density around this type of SWCNT. Moreover, a comparison of the material separated in-house by chromatography to those purchased from a commercial source shows that the in-house material is capable of adsorbing 26.5 to 60% more adsorbate versus the commercial material in which the SWCNTs were separated using density gradient ultracentrifugation methods. This demonstrates that chromatography techniques potentially yield a more effective separation of the semiconducting and metallic SWCNTs. Such opportunities can be influential in the development of new adsorbent systems towards removal of targeted compounds from aqueous environments.